Alat Pendeteksi Detak Jantung dan Kesehatan Berbasis Arduino - Saiful Sufri; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
The heart is a human organ that pumps blood. The heart contracts, where one contraction cycle is usually called a heartbeat. Calculation of heart rate is often done manually by counting the pulse on the wrist for one minute. This method is considered inaccurate because it only relies on the human sense of touch. By making it easier to calculate the heart rate with the Electrocardiograph (ECG) device only but this tool is used in hospitals and cannot be moved. With a sensor that makes daily activities easier. For example, a pulse sensor that is easily available is a pulse sensor that can be used to detect the human heartbeat. With the heart rate device that can be moved using a pulse sensor. Where in the tool that in this final project detects the heart rate will be displayed on the Liquid Crisytal Display (LCD) where the detection results displayed are the results of the detection of human heartbeats accompanied by diseases that may be experienced from heart rate abnormalities.